Nonlinear optical response of first-row transition metal doped Al12P12 nanoclusters; a first-principles study. (April 2021) - Ullah, Faizan; Irshad, Sundus; Khan, Saima; Hashmi, Muhammad Ali; Ludwig, Ralf; Mahmood, Tariq; Ayub, Khurshid
Abstract: The influence of first-row transition metals on structural, electronic, and nonlinear optical (NLO) properties of aluminum phosphide (Al12 P12 ) inorganic fullerene is investigated through DFT methods. The designed M@Al12 P12 composites are thermodynamically quite stable. Frontier orbital analysis revealed that HOMO–LUMO energy gap of Al12 P12 nanocluster is fairly reduced in the presence of transition metals which is mainly attributed to the formation of new high HOMO energy levels due to excess electrons. Based on the NBO analysis, the charge is transferred from transition metal to the Al12 P12 nanocluster. The calculated polarizability ( α o ) and the first hyperpolarizability ( β o ) values indicated that nonlinear optical response is remarkably enhanced under the influence of first-row transition metals. These M@Al12 P12 composites possess giant first hyperpolarizabilities in the range of 3.1 × 10 2 –5.9 × 10 6 au. This study may provide valuable insights for the designing of new high-performance materials for optoelectronic devices. Graphical abstract: Image 1 Highlights: Transition metals doping on Al12 P12 nanocluster is studied. The EH−L of M@Al12 P12 composites are significantly reduced. The charge transfer occurred from transition metal to Al12 P12 nanocluster. M@Al12 P12 composites have excellent polarizability and hyperpolarizability properties.